2022
DOI: 10.3390/galaxies10010033
|View full text |Cite
|
Sign up to set email alerts
|

DEATHSTAR—CO Envelope Size and Asymmetry of Nearby AGB Stars

Abstract: Low- and intermediate-mass stars evolve into asymptotic giant branch (AGB) stars near the end of their lives, losing mass through slow and massive winds. The ejected material creates a chemically-rich expanding envelope around the star, namely the circumstellar envelope (CSE). Investigating the anisotropy of the mass-loss phenomenon on the AGB is crucial in gaining a better understanding of the shaping of the CSE during the transition from AGB star to planetary nebula (PN). We investigate possible signs of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…2) suggests that it has a tenuous CSE. This star is rather wellstudied in CO line emission, and its MLR has been reliably estimated to be of the order of 10 −7 M ⊙ yr −1 (Maercker et al 2016;Andriantsaralaza et al 2021; our estimate for its presentday MLR, see Table 1, is in agreement with this value). Highangular-resolution molecular line studies suggest that R Dor has a low-mass close-in companion, and that this may have an effect on the structure of its CSE, at least on the inner parts (Vlemmings et al 2018).…”
Section: R Doradussupporting
confidence: 83%
See 1 more Smart Citation
“…2) suggests that it has a tenuous CSE. This star is rather wellstudied in CO line emission, and its MLR has been reliably estimated to be of the order of 10 −7 M ⊙ yr −1 (Maercker et al 2016;Andriantsaralaza et al 2021; our estimate for its presentday MLR, see Table 1, is in agreement with this value). Highangular-resolution molecular line studies suggest that R Dor has a low-mass close-in companion, and that this may have an effect on the structure of its CSE, at least on the inner parts (Vlemmings et al 2018).…”
Section: R Doradussupporting
confidence: 83%
“…Multiple IRAS studies report it as having an extended structure at 60 and 100 µm (Fouque et al 1992;Young et al 1993), andWhitelock (1994) reported some optical nebulosity around the star that might be related to the extended FIR structure. More recently Andriantsaralaza et al (2021) observed the CSE of RZ Sgr in CO(J = 2-1) and (J = 3-2) emission, using the Atacama Compact Array. They report an inner CO CSE, with a size of ≈6600 AU, which shows signs of anisotropies (mainly towards the north with respect to the star) and even a potential extended spiral structure.…”
Section: Rz Sagittariimentioning
confidence: 99%
“…Results to date show that large-scale asymmetries and complex velocity profiles are common. Future radiative transfer modeling is underway to determine accurate mass-loss rates and temperature distributions of the gas for the sample (Ramstedt et al 2020;Andriantsaralaza et al 2021). Meanwhile, the NESS § program has been conducting a volume-limited survey of ∼850 evolved stars in CO and in the sub-mm continuum using the APEX and JCMT telescopes, with the goal of measuring outflow parameters, gas-to-dust ratios, and other information critical for characterizing the mass-loss histories of a large sample of stars (Sciclula et al 2022).…”
Section: Insights From Studies Of Large-scale Circumstellar Ejectamentioning
confidence: 99%